A study of the effect of acid immersion on some physical properties of ( Epoxy – MgO) composites - H. Jabir, Jinan M. (Iraqi Journal of Physics, 2019)
In this study a polymeric composite material was prepared by handlay-up technique from epoxy resin as a matrix and magnesium oxide(MgO) as a reinforcement with different weight fraction (5,10,15,and 20)% to resin. Then the prepared samples were immersed undernormal condition in H2So4(1 M) solution, for periods ranging up to10 weeks. The result revealed that the diffusion coefficientdecreasing as the concentration of MgO increase. Also we studiedHardness for the prepared samples before and after immersion. Theresult revealed that the hardness values increase as the concentrationof MgO increase, while the hardness for the samples after immersionin H2SO4 decreased as compared to those before immersion. Inaddition, the dielectric strength decreasing by increasing the MgOconcentration with time immersion.